ANALISIS CUSTOMER RELATIONSHIP MANAGEMENT (CRM) TERHADAP LOYALITAS PELANGGAN DENGAN KEPUASAN PELANGGAN SEBAGAI VARIABEL INTERVENING PADA PELANGGAN CV. CIPTA ADHI NUGRAHA CREATIVE (Lembaga Pengembangan Kinerja Dosen, 2022)
The purpose of this study was to analyze the relationship of Customer Relationship Management (CRM) to customer loyalty and customer satisfaction as an intervening variable. The independent variable analyzed in this research is Customer Relationship Management. The dependent variable analyzed in this study is customer loyalty. The intervening variable in this study is customer satisfaction. The sample used in this study consisted of 160 CAN Creative customers. Sampling was done by purposive sampling method by distributing questionnaires. The data analysis in this study used the Structural Equation Modeling (SEM) analysis method. Data analysis in this study used discriminant validity tests, reliability tests, model quality tests, and hypothesis testing with the help of SmartPLS 3 data processing software. The results showed that Customer Relationship Management (CRM) had a positive and significant effect on customer loyalty, Customer Relationship Management (CRM) also had a significant positive effect on customer satisfaction and customer satisfaction had a significant positive effect on customer loyalty. Another result of this research is that Customer Relationship Management (CRM) has a significant positive effect on customer loyalty through customer satisfaction as an intervening variable.